Question Peter’s dog weighs 12 pounds more than Joe’s dog. The dogs weigh 36 pounds all together. Write an equation to find the weight of Joe’s dog.

Answer: x + x + 12 = 36, 12 pounds Step-by-Step Explanation: Let Joe’s dog’s weight be ‘x’ pounds Peter’s dog’s weight be ‘x + 12’ pounds Both dogs weigh 36 pounds together. Therefore,x + x + 12 = 362x + 12 = 362x = 36 – 122x = 24x = 24/2=> x = 12 Joe’s Dog’s Weight = x => 12Peter’s Dog’s Weight = x + 12 => 24 Log in to Reply

Answer: x + x + 12 = 36, 12 pounds

Step-by-Step Explanation:

Let Joe’s dog’s weight be ‘x’ pounds

Peter’s dog’s weight be ‘x + 12’ pounds

Both dogs weigh 36 pounds together.

Therefore,

x + x + 12 = 36

2x + 12 = 36

2x = 36 – 12

2x = 24

x = 24/2

=> x = 12

Joe’s Dog’s Weight = x => 12

Peter’s Dog’s Weight = x + 12 => 24